A Multiplexed Single-Cell CRISPR Screening Platform Enables Systematic Dissection of the Unfolded Protein Response - Adamson, Britt; Norman, Thomas M.; Jost, Marco; Cho, Min Y.; Nuñez, James K.; Chen, Yuwen; Villalta, Jacqueline E.; Gilbert, Luke A.; Horlbeck, Max A.; Hein, Marco Y.; Pak, Ryan A.; Gray, Andrew N.; et al. (Cell, 2016)
Functional genomics efforts face tradeoffs between number of perturbations examined and complexity of phenotypes measured. We bridge this gap with Perturb-seq, which combines droplet-based single-cell RNA-seq with a strategy for barcoding CRISPR-mediated perturbations, allowing many perturbations to be profiled in pooled format. We applied Perturb-seq to dissect the mammalian unfolded protein response (UPR) using single and combinatorial CRISPR perturbations. Two genome-scale CRISPR interference (CRISPRi) screens identified genes whose repression perturbs ER homeostasis. Subjecting ∼100 hits to Perturb-seq enabled high-precision functional clustering of genes. Single-cell analyses decoupled the three UPR branches, revealed bifurcated UPR branch activation among cells subject to the same perturbation, and uncovered differential activation of the branches across hits, including an isolated feedback loop between the translocon and IRE1α. These studies provide insight into how the three sensors of ER homeostasis monitor distinct types of stress and highlight the ability of Perturb-seq to dissect complex cellular responses. [Display omitted] •Perturb-seq allows parallel screening with rich phenotypic output from single cells•Simultaneous delivery and identification of up to three CRISPR perturbations•Genome-scale screens dissect the mammalian unfolded protein response•Analytical methods separate perturbation responses from confounding effects A strategy for barcoding CRISPR-mediated perturbations allows pooled expression profiling via single-cell RNA sequencing. Application to the mammalian unfolded protein response then enabled systematic delineation of the transcriptional arms of the response and functional clustering of genes affecting ER homeostasis.